A afro-brasilidade na música para canto e piano no Ciclo Beiramar, op. 21, de Marlos Nobre - Robson Lopes (2010)
This thesis consists of a study on afro-Brazilian chamber music, which focuses on the analysis of the piece Beiramar, Op. 21, by Marlos Nobre, composed in 1966 and inspired by black songs and beliefs from Bahia. We approach the complexity of the representation of black cultures in the scope of classical music, by taking into account the historical processes of appropriation and re-signification they have undergone. History, culture and diversity are elements which determine the way not only an individual but also a piece of music belongs to the culture that produces it. Our literary and musical analyses furnish instruments for a renewed interpretation both of Marlos Nobre's work and of other afro-Brazilian chamber music pieces